2014
DOI: 10.1016/j.celrep.2014.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Stat5 by FAK and PAK1 in Oncogenic FLT3- and KIT-Driven Leukemogenesis

Abstract: SUMMARY Oncogenic mutations of FLT3 and KIT receptors are associated with poor survival in patients with acute myeloid leukemia (AML) and myeloproliferative neoplasms (MPN) and currently available drugs are largely ineffective. Although Stat5 has been implicated in regulating several myeloid and lymphoid malignancies, how precisely Stat5 regulates leukemogenesis, including its nuclear translocation to induce gene transcription is poorly understood. In leukemic cells, we show constitutive activation of focal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 48 publications
4
66
0
Order By: Relevance
“…However, a role for active STAT5 in metastasis of other cancers has been established, and active STAT5a promotes prostate cancer invasion and migration40. Whilst CaMKII does not phosphorylate STAT5a at the site examined in this study, a FAK-mediated pathway can control STAT5 activation in leukaemia cells41. Furthermore, FAK42 and Akt43 are essential for inducing EMT in hepatocytes and cancer cells, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…However, a role for active STAT5 in metastasis of other cancers has been established, and active STAT5a promotes prostate cancer invasion and migration40. Whilst CaMKII does not phosphorylate STAT5a at the site examined in this study, a FAK-mediated pathway can control STAT5 activation in leukaemia cells41. Furthermore, FAK42 and Akt43 are essential for inducing EMT in hepatocytes and cancer cells, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…FLT3-ITD leads to constitutive activation of JAK/STAT signaling, driving growth and transformation of hematopoietic cells. [35][36][37] In keeping with this, our transcriptome analysis revealed that genes involved in JAK/STAT signaling (Stat5a, Cish, Socs2) were differentially expressed in Figure 8B). We confirmed by RNA-seq that this was due to activation of a JAK/STAT program in Npm1 cA/1 ;Nras G12D/1 AML cells (supplemental Figure 9).…”
Section: Hoxa Gene Expression Is Unaltered In Npm1-mutant Early Multimentioning
confidence: 75%
“…28 Interestingly, 3 of the 4 AML cell lines and several patient samples we tested in this study do not contain either FLT3-ITD or KITD816V mutations yet were still sensitive to PAK1 inhibition. Furthermore, the AML patient samples we studied included FAB subtypes M4 and M5, which more frequently have elevated PAK1 expression from our assessments of a large cohort of AML patients (GSE14468; supplemental Figure 7A-B).…”
Section: Discussionmentioning
confidence: 99%